Adhesives and methods of use
By developing UV curable acrylic adhesives, combined with plasticizers and acrylic-based polymers, the problem of poor bonding performance of existing waterproof sheet materials at low and high temperatures is solved, and efficient bonding effect is achieved under different temperature environments.
Patent Information
- Application Number
- CN202080078960.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-21
- Filing Date
- 2020-09-30
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2040-09-30
AI Technical Summary
The waterproof plate materials used in existing building structures to control the movement of water, water vapor and air have poor bonding performance under low temperature conditions and may lose adhesion at high temperatures, which cannot meet the waterproofing needs of buildings under different temperature environments.
A UV curable acrylic adhesive containing plasticizers and UV curable acrylic-based polymers was developed to maintain adhesive properties at low temperatures and maintain integrity at high temperatures. The adhesive combines components through batch or continuous mixing to form an article with self-adhesive properties.
The adhesive is implemented at low temperatures of 0 degrees Fahrenheit (-18 degrees Celsius) and can maintain adhesion at high temperatures without primer-assisted bonding. It is suitable for a variety of building construction materials, including waterproof tapes, roof liners and barriers.
Smart Images

Figure CN115052926B_ABST
Abstract
Description
[0001] This application claims the benefit of U.S. Provisional Application No. 62 / 907,894, filed on September 30, 2019, and U.S. Provisional Application No. 63 / 054,506, filed on July 21, 2020, the disclosures of which are incorporated herein by reference. Background Art
[0002] The present disclosure relates to waterproof sheet materials employed in building construction, particularly in wall and roof applications to control the movement of water, water vapor and air.
[0003] Modern building structures often use barrier membrane sheet materials to control the flow of moisture in and out of a building and also to control ventilation or air movement through a wall or roof structure. Typical membrane products are designed to be weather resistant, block liquid water, and resist wind pressure.
[0004] However, at the same time some membranes can be formed so that water vapor can pass relatively freely to avoid moisture or condensation problems within a building or within a wall or roof structure. Many water vapor permeable membrane products are available and combine weather resistance with water vapor permeability.
[0005] Previously known waterproof sheets with both waterproof and breathable properties have been developed. An example of such a breathable waterproof sheet is a flash spun nonwoven fabric. For example, U.S. Patent No. 3,169,899 discloses a flash spun nonwoven fabric. U.S. Patent No. 3,532,589 discloses a method for producing a flash spun nonwoven fabric. This nonwoven fabric blocks water but allows water vapor to pass through. An example of a known nonwoven fabric is commercially available from EI Du Pont de Nemours and Company in Wilmington, Delaware, USA under the trade name "Tyvek". Such breathable and breathable waterproof sheets are beneficial to pass ASTM D-1970 / D-1970M or similar modified experiments (such as modified experiment 1 of ASTM D-1970 / D-1970M, modified experiment 2 of ASTM D-1970 / D-1970M, or modified experiment 3 of ASTM D-1970 / D-1970M). In addition to building wraps, the disclosure also has usefulness in connection with at least roof underlayments and flashing tapes.
[0006] Typical membrane sheets are attached to a wall or roof structure by mechanical fasteners (such as screws or nails) or by using an adhesive. The adhesive provided on the barrier film is advantageous in providing strong adhesion under a variety of conditions. For example, such an adhesive is beneficial in adhering to a wet substrate over a wide temperature range (such as 0°F to 150°F). The adhesive composition of the present invention achieves these goals. Summary of the invention
[0007] Various details of the present disclosure are summarized below to provide a basic understanding. The summary is not a broad overview of the present disclosure and is neither intended to identify certain elements of the present disclosure nor to describe the scope of the present disclosure. Instead, the main purpose of the summary is to present certain contents of the present disclosure in a simplified form before presenting a more detailed description below.
[0008] According to a first embodiment, an acrylic (or acrylate polymer) adhesive formulation that can be used in various building construction and / or enclosure applications is provided. The adhesive can be applied to various substrates, such as flashing tapes, vapor permeable membranes, vapor impermeable membranes and roof pads, sealing tapes, double-coated tapes, seaming tapes and flexible / semi-flexible substrates / barriers to make them self-adhesive. The adhesive can be applied at low temperatures of 0 degrees Fahrenheit (-18 degrees Celsius), but can still maintain integrity at high temperatures without sacrificing adhesion to ordinary construction / window opening surfaces. No primer is required to assist adhesion. The adhesive may include a blend of a plasticizer and an ultraviolet (UV) curable acrylic-based polymer that can cross-link the adhesive when exposed to ultraviolet light in a narrow wavelength range.
[0009] According to a second embodiment, an adhesive composition is provided, the adhesive composition comprising a UV-curable acrylic polymer having a molecular weight between about 150,000 and 300,000 g / mol or between about 170,000 and 250,000 g / mol and 1 to 50 wt%, 2 to 30 wt%, 5 to 25 wt%, or 8 to 20 wt% of a plasticizer, the UV-curable acrylic polymer having a molecular weight between about 200 and 1000 g / mol, between 300 and 700 g / mol, or between 400 and 600 g / mol.
[0010] According to a third embodiment, the adhesive comprises a non-reactive liquid plasticizer, resin and / or tackifier (e.g., 8 to 20 wt%) having a first Tg and a UV reactive acrylic polymer (e.g., 80 to 92 wt%) having a Tg higher than the first Tg. An example of a liquid plasticizer is Citroflex A4 commercially available from Vertellus. An example of a UV reactive acrylic polymer is AcResin 260 commercially available from BASF. The UV reactive acrylic polymer may have a weight average molecular weight (M) of at least 150,000 or at least 170,000 g / mol. w ), which is measured by gel permeation chromatography (GPC), for example a Walters Breeze II system with a Styralgel, HR1+E1 column using 30 mg of binder dissolved in 10 ml of THF.
[0011] According to a further embodiment, a barrier article for use in building construction is provided. The article includes a flexible substrate that is at least substantially impermeable. The substrate has a width of at least 60 cm, a length of 5 m, and a thickness of 0.001 inches. The substrate includes a pressure sensitive adhesive deposited on at least one major surface. The adhesive can be in the form of a repeating pattern covering less than 100% of the major surface. The adhesive can include a mixture of a UV curable acrylic polymer and at least 8% by weight of a plasticizer. The adhesive can be formed by combining the components using intermittent or continuous / in-process mixing.
[0012] According to another embodiment, an adhesive composition is provided, the adhesive composition comprising a UV curable polymer and a plasticizer, the UV curable polymer having a molecular weight of at least 150000 g / mol and a λ of 200 to 360 nm or 250 to 260 nm. 最大 , the plasticizer absorbs less than 5% of UV radiation at a lambda of 200 to 360 nm or 250 to 260 nm.
[0013] In an optional embodiment, the adhesive may include a non-reactive liquid plasticizer, resin and / or tackifier having a first Tg (e.g., 1 to 50 wt. % or 2 to 30 wt. % or 5 to 25 wt. % or 8 to 20 wt. %) and a UV reactive acrylic polymer having a Tg higher than the first Tg (e.g., 70 to 99 wt. %). Including a small amount of a low (i.e., lower than the primary plasticizer) Tg plasticizer, resin or tackifier can advantageously provide the desired adhesive properties in a low temperature environment. The adhesive polymer may have a number average molecular weight (M) between 50,000 and 65,000 g / mol. n ) and / or a weight average molecular weight (M) measured by gel permeation chromatography (GPC) between 100,000 and 300,000 g / mol or between 150,000 and 300,000 g / mol or between 100,000 and 200,000 g / mol. w ), for example a Walters Breeze II system with a Styralgel, HR1+E1 column using 30 mg of binder dissolved in 10 ml of THF.
[0014] The adhesives of the present disclosure are suitable for use in building construction materials such as vapor permeable and vapor impermeable barriers, flashing tapes, sealing tapes, transfer films, double-coated tapes, roofing pads, and flexible / semi-flexible substrates. The adhesive can be applied to the building material in a repeating or random pattern that covers 100% or less of the surface in a selected proportion to impart controlled permeability, adhesion, and functionality.
[0015] Adhesive can be formed by combining components using mixing in intermittent or continuous / process.Can be by cured UV pressure-sensitive adhesive transfer coating on the described goods, or by directly coating and curing pressure-sensitive adhesive on goods to form adhesive comprising goods.Transfer coating substrate can form release liner (release liner, or be called anti-adhesive liner or peeling liner) on goods.Can remove transfer coating substrate and replace with the release liner of alternative composition.Can treat goods to allow self-winding (self-winding, or be called self-bending or self-winding), wherein remove transfer coating substrate after the UV curing of adhesive.
[0016] According to a further embodiment, an adhesive composition is provided, comprising a UV-curable polymer having a shear viscosity (Pa.s) of less than 17 at 240°F and less than 10 at 280°F in combination with 5 to 30 wt % or 5 to 25 wt % of a plasticizer, the plasticizer having a molecular weight between about 200 and 600 g / mol.
[0017] According to another embodiment, an article is provided, comprising a flashing tape, a vapor barrier, or a roof underlayment, the article comprising 100% adhesive coverage using an adhesive of the present disclosure on an adhesive containing surface. The article can be vapor permeable after being attached to a building substrate. For example, in the case of a permeable nonwoven polyolefin substrate (optionally microporous), the adhesive containing article can include (i) at least 3 mils of adhesive and having an ASTM E96B permeability of at least 40, (ii) at least 5 mils of adhesive and having an ASTM E96B permeability of at least 25, or (iii) at least 8 mils of adhesive and having an ASTM E96B permeability of at least 10 or 15.
[0018] According to further embodiments, a release liner comprising paper, polymer or other material is provided.The release liner comprising adhesive is a self-winding material or liner used as an adhesive transfer product. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The following is a brief description of the drawings, which are presented for the purpose of illustrating and not limiting the exemplary embodiments disclosed herein.
[0020] Figure 1 is a perspective view of a representative barrier laminate;
[0021] Figure 2 is along Figure 1 an enlarged cross-sectional view taken along line 2-2 of FIG.
[0022] Figure 3 is to accommodate Figure 1A partial view of a building with a barrier laminate, the barrier laminate being applied to the building;
[0023] Figure 4 is a front plan view of an exemplary adhesive application pattern;
[0024] Figure 5 is a graphical depiction of the shear viscosity of a representative UV curable polymer;
[0025] Figure 6 is a graphical depiction of the UV absorbance of various resin / plasticizer blends; and
[0026] Figure 7 The hot shear performance of AC resin / Citroflex A4 adhesive blends is shown. DETAILED DESCRIPTION
[0027] A more complete understanding of the components, methods, and devices disclosed herein may be obtained by referring to the accompanying drawings, which are merely schematic representations based on convenience and ease of presenting the present disclosure and are therefore not intended to indicate the relative sizes and dimensions of the devices or their components and / or to define or limit the scope of the exemplary embodiments.
[0028] Although specific terms are used in the following description for the sake of clarity, these terms are intended to refer only to specific structures selected for illustrating the embodiments in the drawings, and are not intended to define or limit the scope of the present disclosure.
[0029] The singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise.
[0030] As used herein, the terms about, generally, and substantially are intended to cover modifications of structure or numbers that do not significantly affect the purpose of the element or number modified by such terms. The terms "about" or "approximately" with respect to a value or shape refer to + / -10% of a value, property, or characteristic, but expressly include the exact value. The term "substantially" with respect to a property or characteristic refers to a property or characteristic that is expressed to a greater extent than the opposite of the property or characteristic. For example, a "substantially" transparent plasticizer refers to a material that transmits more radiation (e.g., ultraviolet light) than it does not transmit (e.g., absorbs and reflects).
[0031] Reference now Figure 1 and 2 A first embodiment of a barrier laminate is designated by reference numeral 10. The barrier laminate 10 is suitable for attachment to an exterior surface of a structure, such as Figure 3The house 12 shown. The sheathing 11 is applied before the sidewalls are fitted to cover the joints 13 between structural members and between adjacent sheathing members 11, window frames 15, door frames 16, door sills 17, corners, overhangs, raised heel trusses and strip joists, etc., which are assembled to form the structure or house 12. Although Figure 3 While depicted in the figure, the main flexible barrier pad is also suitable for roof and commercial building applications.
[0032] The barrier laminate 10 includes a flexible, elongated barrier 18 having opposing edges 20 and opposing first and second major surfaces 21, 22. The barrier 18 may be a porous material such that the barrier 18 has microchannels between its major surfaces 21 and 22 to provide for the passage of water vapor between its major surfaces while limiting the passage of liquid water and air between its major surfaces 21 and 22. The barrier laminate 10 also includes a layer 24 of a discontinuous pressure-sensitive adhesive for bonding the barrier layer 18 to a structural member. Specifically, the adhesive portions 24 are separated by adhesive-free portions 28 to prevent the adhesive from interfering with the movement of water vapor through the barrier layer 18.
[0033] The sheet can be water impermeable and water vapor permeable or water vapor impermeable. A water vapor permeable sheet can be microporous, microperforated, or some other type of vapor permeable sheet or film. A microporous sheet can be a non-perforated continuous microfiber web whose micropores are large enough to allow water vapor to pass through, but small enough to resist air and liquid water. Microperforated films rely on mechanical pinning perforations and / or film lamination to establish performance.
[0034] Suitable microporous sheets can be spunbonded or fiber-bonded polyolefins, such as described in U.S. Pat. Nos. 3,532,589 and 5,972,147, the disclosures of which are incorporated herein by reference. Exemplary polyolefins are polyethylene and polypropylene. A commercially available microporous sheet is sold under the trademark Tyvek. Other suitable microporous sheets include oriented polymer films such as described in U.S. Pat. No. 5,317,035, incorporated herein by reference, which contain ethylene-propylene block copolymers. An exemplary film is commercially available from the RKW Group under the trademark Aptra.
[0035] For the purpose of improving strength and other physical properties, the sheet material can be reinforced with various types of scrim materials, or can be laminated to other sheets or films (such as nonwoven polypropylene or nonwoven polyester). Suitable sheet materials can be multi-layer laminates including microporous or microperforated layers (e.g., polyethylene). Examples of such sheet materials are Utraperm Lite or Ultraperm Max provided by Industrial Textiles and Plastics, UK.
[0036] Typical water barrier films will be supplied in roll form and have a width (cross direction or XD) in the range of about 30 to 250 cm, more typically in the range of about 60 to 160 cm; and a length (machine direction or MD) of about 5 to 80 m, more typically about 15 to 40 m. In general, the film will typically have a thickness of 0.001 to 0.008 or 0.001 to 0.025 inches.
[0037] Other suitable applications for the subject adhesives include use with roofing underlayments and flashing tapes.
[0038] A roof underlayment can generally be described as a sheet inserted between the roof deck or other substrate of a building structure and the bottom surface of a roof membrane. The underlayment sheet provides both water resistance and can have a flame retardant effect on the spread of fire. In addition, it can provide a temporary waterproof roof membrane without the need for any other membrane material. Exemplary roof underlayments are described in US 6,641,896; US 9,415,563; US 9,702,148, the disclosures of which are incorporated herein by reference.
[0039] With respect to flashing tapes, it is noted that many construction projects typically require the installation of self-adhesive flashing tapes on fenestration joints, i.e., joints between penetrations (such as windows, doors, vents, etc.), and building structures, as well as on various surfaces near or within windows, to seal water. These flashing tapes may be applied prior to installing siding or trim. Nails used to attach siding or trim to building structures are often installed through flashing tapes, which can help seal such penetrations. Exemplary flashing tapes are described in U.S. Publications 2012 / 0085063 and 2013 / 0139953, the disclosures of which are incorporated herein by reference.
[0040] The adhesive can be deposited onto the substrate carrier sheet by any means. One exemplary method is by transfer, such as by using an engraved roller. A suitable example is a gravure roller. One advantage of using a gravure roller is that the adhesive can be deposited onto the substrate carrier sheet at a low application rate, which can be precisely controlled in terms of thickness and coverage area. The method is described in PCT / US2019 / 029807, the disclosure of which is incorporated herein by reference.
[0041] Alternatively, substrate transfer coating may be used, wherein the adhesive is first spread onto a release substrate to form a film. The adhesive may be UV cured on the release substrate, and then at least a portion of the cured adhesive film may be laminated to a building envelope substrate (e.g., a roofing pad, a vapor barrier, or a flashing tape). It may be advantageous to cure the adhesive on the transfer substrate to avoid damaging the work material. Presumably, the release substrate may then form a release liner on the building envelope substrate containing the adhesive. The presence of the release liner may allow the building envelope substrate to be stacked or rolled (or otherwise referred to as rolled) on itself.
[0042] In some embodiments, the pressure sensitive adhesive is disposed discontinuously in a patterned manner. In some embodiments, the pressure sensitive adhesive covers 10% to 90% of the surface. The adhesive may be appropriately applied to cover between 25% and 90% of the area, or between 50% and 80% of the area, to obtain the best balance of adhesion and vapor permeability in the sheet. In some embodiments, the pressure sensitive adhesive is a permeable pressure sensitive adhesive disposed continuously over the entire surface.
[0043] The adhesive may be applied at a thickness of 0.001 inch to 0.1 inch, or 0.003 inch to 0.025 inch, or 0.005 inch to 0.02 inch. The adhesive may be protected with a peelable release sheet or liner to enable roll packaging. Suitable release sheets are paper sheets, coatings with silicone release surfaces, and some treated plastic films. Optionally, the back major surface of the barrier article may include a covered or coated low surface energy release layer or a low adhesion back coating.
[0044] From the production point of view, the adhesive can be a hot melt type. An example of a suitable adhesive composition is polyacrylate. This is an addition polymer that can be obtained by free radical polymerization of acrylic monomers, which are understood to include methacrylic monomers, with or without other copolymerizable monomers. Polyacrylate can be composed of at least 40% by weight, or at least 60% by weight, or at least 80% by weight of (meth) acrylic acid C1-C18 alkyl esters. For example, (meth) acrylic acid C1-C18 alkyl esters, such as methyl (meth) acrylate, ethyl (meth) acrylate, n-butyl (meth) acrylate, 2-ethylhexyl (meth) acrylate are suitable.
[0045] Acrylate or methacrylate polymers can be prepared by polymerizing alkyl or hydroxyalkyl acrylates or methacrylates, optionally with one or more nitrogen-containing monomers and / or carboxylic acids. Acrylates or methacrylates include those having from about 1 to about 24, or from about 2 to about 18, or from about 4 to about 16 carbon atoms in the ester group. Alkyl acrylates and alkyl methacrylates include, but are not limited to, 2-ethylhexyl acrylate, isooctyl acrylate, butyl acrylate, sec-butyl acrylate, methyl butyl acrylate, 4-methyl 2-pentyl acrylate, isodecyl methacrylate, and hydroxy substituted analogs thereof, and mixtures thereof.
[0046] Polymer can include other copolymerizable monomers.Usually, these monomers exist with the amount of 0 wt % to about 33 wt % or about 1 wt % to about 20 wt % or about 3 wt % to about 15 wt %.Can select these other monomers to adjust the glass transition temperature of polymer.Other monomers include polystyryl ethyl methacrylate, acetoacetoxy ethyl methacrylate, alpha olefin (for example C2-8 alpha-olefin), such as ethylene, propylene and butylene, and the vinyl ester containing the alkanoic acid more than three carbon atoms.The example of other monomers that can form adhesive is the vinyl ester containing the carboxylic acid of up to 20 carbon atoms, the vinyl aromatic hydrocarbon with up to 20 carbon atoms, ethylenically unsaturated nitrile, vinyl halide, the vinyl ether containing the alcohols of 1 to 10 carbon atoms, the aliphatic hydrocarbon with 2 to 8 carbon atoms and 1 or 2 double bonds, or the mixture of these monomers.
[0047] The polymers can be synthesized in solution, emulsion and / or bulk polymerization.
[0048] The polymer can be crosslinked with UV light. For UV crosslinking, the composition of the invention can have a photoinitiator added thereto. Alternatively, the photoinitiator can be attached to the polymer.
[0049] By exposure to high-energy light, especially UV light, the photoinitiator causes crosslinking of the polymer, for example by chemical grafting of the photoinitiator to spatially adjacent polymer chains. Advantageous wavelengths of light are about 200 to 360 nm. Advantageous energy levels are about 20 mJ / cm 2 and 100mJ / cm 2 between.
[0050] Crosslinking can be performed by inserting the carbonyl group of the photoinitiator into adjacent CH bonds to form CC OH groups. The composition may contain 0.0001 to 1 mol, or 0.0002 to 0.1 mol, 0.0003 to 0.01 mol of photoinitiator or a group used as a photoinitiator and attached to the polymer per 100 grams of polyacrylate. For example, the photoinitiator includes acetophenone, benzophenone, benzoin ether, benzyl dialkyl ketal or a derivative thereof.
[0051] The photoinitiator can be incorporated into the polymer chain by free radical copolymerization. For this purpose, the photoinitiator can include an acrylic acid or methacrylic acid group. Suitable copolymerizable photoinitiators are acetophenone derivatives or benzophenone derivatives containing at least one ethylenically unsaturated group. The ethylenically unsaturated group is preferably an acrylic acid or methacrylic acid group. The ethylenically unsaturated group can be directly attached to the benzene ring of the acetophenone or benzophenone derivative. There can be a spacer group between the benzene ring and the ethylenically unsaturated ring.
[0052] Polymer adhesives have poor adhesion at low temperatures because at these temperatures, the storage modulus and loss modulus are too high for the adhesive to flow onto any surface. Based on dynamic mechanical analysis, an exemplary UV-curable acrylic-based polymer has a glass transition temperature (Tg) of -39 degrees Celsius and a Dahlquist temperature of -6 degrees Celsius. The adhesive temperature can be above its Dahlquist temperature to provide adequate tack and flowability on a surface.
[0053] To lower the Tg and Dahlquist temperature of the UV-curable acrylic polymer, a plasticizer may be added. The plasticizer is selected to provide (1) sufficient chemical compatibility with the acrylic polymer so that no significant phase separation occurs, resulting in no loss of adhesive properties, and the resulting mixture is optically clear for proper UV curing, (2) sufficiently low volatility so that plasticizer migration is minimal during storage in the building envelope to avoid loss of adhesive properties over time, (3) a refractive index similar to that of the acrylic polymer to allow for proper UV curing of the base acrylic polymer, (4) a low molecular weight to allow diffusion of plasticizer molecules between the acrylic polymers during mixing in a continuous mixer (short mixing cycles and high production speeds), and (5) low toxicity and low odor for environmental, health, and safety benefits.
[0054] Plasticizer can be a high boiling point solvent or a softener, usually a liquid. The molecular weight can be between 200g / mol and 600g / mol. Plasticizer can be adipic acid ester, phosphoric acid ester, benzoic acid ester or phthalic acid ester, polyalkylene oxide, sulfonamide etc. Plasticizer can be selected from the group consisting of an ester of a C2-C4 carboxylic acid and a C2-05 alkyl alcohol with 2 to 4 hydroxyls, the alkyl alcohol being for example ethylene glycol, propylene glycol, glycerine, trimethylolpropane or pentaerythritol, optionally ethoxylated, the acetate of C2-05, such as for example glyceryl triacetate or ethylene glycol diacetate. Plasticizers include, but are not limited to, DOA plasticizers (dioctyl adipate), TEG-EH plasticizers (triethylene glycol di-2-ethyl hexanoate), TXIB plasticizers (2,2,4,-trimethyl-1,3-pentanediol diisobutyrate), DEP plasticizers (diethyl phthalate), DOTP plasticizers (dioctyl terephthalate), DMP plasticizers (dimethyl phthalate), DOP plasticizers (dioctyl phthalate), DBP plasticizers (dibutyl phthalate), polyethylene oxide, toluenesulfonamide, dipropylene glycol benzoate, and the like. Specific examples include trioctyl trimellitate; adipates such as dimethyl adipate; and benzoates such as diethylene glycol dibenzoate. Other exemplary plasticizers include citrates, acetates, monomeric adipates, adipates of polymeric esters, trimellitates, and trimalates. Commercially available citrate esters are CITROFLEX A-4, CITROFLEX B6 and CITROFLEX A-2 from Vertellus. Commercially available acetate esters are TRIACETIN from Eastman Chemical. Commercially available polymeric esters and monomeric adipates are ADMEX sold by Eastman Chemical. Suitable trimellitate esters are commercially sold as TOTM by Hallstar Corporation.
[0055] The adhesives of the present disclosure may also include one or more crosslink enhancers to improve high temperature performance and cured tack at higher coating weights (eg, 6 to 10 mils). Exemplary crosslink enhancers include SR351 and SR 355 from Sartomer.
[0056] Tackifying resins are useful in adhesives and may include aliphatic, aromatic or mixed aliphatic aromatic hydrocarbon resins and hydrogenated derivatives thereof, as well as terpenes and terpene derivatives having a Ring and Ball softening point between about 70° C. and about 150° C. Those skilled in the art will recognize that these tackifying resins having different levels of hydrogenation are useful.
[0057] Paraffin waxes can be used in the adhesive and include paraffin waxes with a melting point in the range of about 130 to 200°F (54°C to 193°C), such as, for example, PACEMAKER from Citgo, and R-2540 from Moore and Munger; low melting synthetic microcrystalline or Fischer-Tropsch waxes with a melting point below about 180°C. Most preferably, the wax is a paraffin wax with a melting point of 150°C.
[0058] The adhesive of the present invention may also contain a stabilizer or antioxidant. Among the applicable stabilizers or antioxidants, high molecular weight hindered phenols and multifunctional phenols are included herein, such as sulfur- and phosphorus-containing phenols. Hindered phenols are well known to those skilled in the art and can be characterized as phenolic compounds that also contain steric macromolecular free radicals near their phenolic hydroxyl groups. Specifically, tert-butyl groups are typically substituted to at least one ortho position on the benzene ring relative to the phenolic hydroxyl group. These steric macromolecular substituent groups present near the hydroxyl group help to retard its stretching frequency and correspondingly retard its reactivity; this hindrance therefore provides stable performance for the phenolic compound. Representative hindered phenols include: 1,3,5-trimethyl 2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene; pentaerythritol tetrakis-3(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; n-octadecyl 3(3,5-di-tert-butyl-4-hydroxyphenyl)-propionate; 4,4'-methylenebis(2,6-tert-butylphenol); 4,4'-thiobis(6-tert-butyl-o-cresol); 2,6-di-tert-butylphenol; 6-(4-hydroxyphenoxy)-2,4-bis(n-octylthio)-1,3,5 triazine; di-n-octylthioethyl 3,5-di-tert-butyl-4-hydroxy-benzoate; and sorbitol hexa[3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionate]. Commercially available antioxidants include hindered phenols known as IRGANOX and available from Ciba-Geigy.
[0059] Other additives conventionally added to hot melt adhesives for various end uses, such as pigments and dyes, may also be added to the formulations of the present invention in smaller amounts (ie, up to about 10% by weight).
[0060] The adhesive composition can be prepared by blending the components in a melt at an elevated temperature until a homogeneous blend is obtained. Various blending methods are known in the art and any method that produces a homogeneous blend is satisfactory.
[0061] In situations where low temperature installation of flashing tapes, vapor membranes or roof underlayments is required, it has been found that a specific molecular weight range of UV curable acrylic polymers can be advantageous. In addition, two UV curable polymers including AcResin 250 and AcResin 260 were evaluated. The molecular weight was measured by gel permeation chromatography (GPC), for example using a Walters Breeze II system with a Styralgel, HR1+E1 column, using 30 mg of adhesive dissolved in 10 ml of THF. The results are as follows:
[0062]
[0063] Compared with AcResin 250, AcResin 260 has a slightly lower molecular weight M n (number average molecular weight) and M w (weight average molecular weight). For example, the weight average molecular weight of AcResin 260 is 196,000 g / mol, while the weight average molecular weight of AcResin 250 is 209,000 g / mol. At 240°F, 260°F, and 280°F, the shear viscosity values of AcResin 260 are significantly lower than those of AcResin 250.
[0064] The shear viscosity of UV-curable polymers was compared in a capillary rheometer at different temperatures. Figure 5 Shear viscosity is shown at a shear rate of 5000 (1 / s) using a Malvern Instruments RH7 capillary rheometer.
[0065] Presumably, an article such as a flashing tape, vapor barrier, or roofing underlayment will include 100% adhesive coverage on the adhesive containing surface. The article may be vapor permeable when attached to a building structure because the adhesive may be at least partially vapor permeable.
[0066] Adhesive composition examples
[0067] AAMA 711 is the building specification for flashing tape. Adhesion to various surfaces is preferably at least 1.5 lbs / inch. Oriented strand board (OSB) is a common fenestration surface, but one of the most difficult fenestration surfaces to adhere to due to its low surface energy and rough surface. The performance of a typical commercial UV curable acrylic-based polymer at various UV doses is shown below. A 5 mil thick base polymer adhesive was laminated to an 8 mil thick flashing. Bonding to OSB using only the base polymer adhesive met the standard at room temperature, but did not bond well at 0 or 10 degrees Fahrenheit.
[0068]
[0069] To achieve improved low temperature positioning, a plasticizer was blended with a curable acrylic-based polymer. The blended adhesive had a thickness of 5 mils and was laminated to an 8 mil flashing. The adhesive was subjected to different UV doses to cure the UV curable acrylic-based polymer. Increasing the weight % of plasticizer increased adhesion at both 0 and 10 degrees Fahrenheit.
[0070]
[0071] The table below shows the use of different weight percentages of CITROFLEX B-6 citrate plasticizer subjected to different UV doses. The blend consists of plasticizer and UV curable acrylic based polymer. Increasing the weight % of plasticizer increases adhesion at both 0 and 10 degrees Fahrenheit.
[0072]
[0073] The following table shows the use of different weight percentages of Admex 525 polymer adipate plasticizer subjected to different UV doses to cure the base acrylic polymer. The blend consists of plasticizer and UV curable acrylic based polymer. Increasing the weight % of plasticizer increases adhesion at both 0 and 10 degrees Fahrenheit.
[0074]
[0075] The following table shows the results of the experiment at 14 wt% of Citroflex A-4 at 120 mJ / cm 2 Adhesion of a blend of Citroflex A-4 and a UV curable acrylic based polymer cured at 10°C to various surfaces. One aging condition of the adhesive was aging for 16 hours at 150°F, 80% relative humidity. The second aging condition of 36 hours was aging for 36 hours at 150°F, 60% relative humidity. These aging conditions simulate storage for several years in a humid warehouse environment. Of particular interest is that if there is any plasticizer migration, this will severely degrade the adhesive performance. The adhesive was aged and then applied to the various surfaces shown below. The adhesive still maintained adhesion above the required specification at 10°C and maintained integrity at higher temperatures as shown by Shear / Steel at 149°F and SAFT.
[0076]
[0077] UV Curing Example
[0078] Ultraviolet (UV) spectrophotometry can measure the concentration of photoreactive groups (or photoinitiators) in UV curable adhesives such as AcResin 250 and AcResin 260 from BASF and can therefore be used for quantitative analysis. 最大 It has been determined to be approximately 255nm. To obtain low temperature performance, AcResin 250 or AcResin 260 can be modified with a low Tg plasticizer. The results show that the choice of plasticizer can play a role in the cure of the photoreactive groups of the AcResin 250 and AcResin 260 polymers. If the plasticizer absorbs light at 255nm, it will compete with the photoreactive groups in AcResin 250 or AcResin 260, resulting in reduced UV cure.
[0079] Plasticizers used in this study:
[0080] ID Physical state Functionality Triacetin Liquid ester Citroflex A4 Liquid ester Benzoflex50 Liquid Contains esters of parabens Pycal 94 Liquid Esters containing phenyl groups
[0081] AcResin 250 was blended with various plasticizers at a ratio of 80 / 20 at 280°F for 1 hour to ensure good dispersion. The adhesive blends and neat AcResin were coated on a PET release liner to achieve an adhesive thickness of 5 mils. The coated adhesives were cured under UV light using a Puck to achieve a UVC dose of 167 mJ.
[0082] The cohesive strength of various adhesives is shown in the table below.
[0083] ID Cohesion AcResin 250 only good 80%AcResin 250-20%Triacetin good 80% AcResin 250-20% Citroflex good 80% AcResin 250-20% Benzoflex Difference 80%AcResin 250-20%Pycal 94 Difference
[0084] AcResin 250, an 80 / 20 blend of AcResin 250 / Triacetin, and an 80 / 20 blend of AcResin 250 / Citroflex A4 have good cohesive strength. However, an 80 / 20 blend of AcResin 250 / Benzoflex 50 and an 80 / 20 blend of AcResin 250 / Pycal 94 have poor cohesive strength.
[0085] The cured adhesive was manually laminated onto a quartz plate to measure UV absorbance. The absorbance of the cured adhesive sample was measured at 255 nm using a UV-visible spectrometer (Perkin Elmer Lambda 465PDA). Figure 6 as shown in the chart.
[0086] AcResin 250 has an absorbance of 1.0, and the addition of Triacetin or Citroflex A4 does not seem to change the absorbance of the blended adhesive. This means that both Triacetin and Citroflex A4 are transparent (also known as passable) to the UV curing process. As a result, the cohesive strength of the cured adhesive is good. On the other hand, both Pycal 94 and Benzoflex 50 have much higher absorbances (Pycal 94=1.7; Benzoflex 50=3.6) than pure AcResin 250 (absorbance=1). This means that both Pycal 94 and Benzoflex 50 are opaque to the UV curing process. The presence of Pycal 94 or Benzoflex 50 plasticizers hinders the UV curing process. Therefore, the cohesive strength of the cured adhesive is poor.
[0087] Low Temperature (CT) Formulation Adhesive Examples
[0088] CT Example 1
[0089] 83 parts of AcResin 260 manufactured by BASF were charged into a planetary mixer preheated to 280°F. 17 parts of Citroflex A4 were slowly added to the mixer and the mixture was stirred at 280°F for 30 minutes. The mixture was then degassed and discharged into a 5 gallon bucket. The resulting adhesive was uniform, clear and free of bubbles.
[0090] 5 gallon buckets containing adhesive are placed under 5 gallon bucket melters Alta Pail II (Nordson company) for UV-hot melt processing. The temperature setting of Alta Pail is 220 ° F, so that the adhesive is melted and pumped to the adhesive container where the temperature remains at 220 ° F. Then, the adhesive is pumped into the slot die from the adhesive container with a thickness of 16 mils. 5 mil adhesives are deposited on 76 pounds of multi-clad release liners, and by UV light chamber (H+ bulb from Heraeus company). The UVC dosage recorded by EIT UV Puck II is 90mJ / cm 2 .
[0091] The interior of 8 mil TPO-based waterproof backing membrane MC900MJZ manufactured by Charter NEX was corona treated to produce a surface energy of 40 dynes / cm2. The cured adhesive was laminated to the corona treated side of the Charter NEX membrane using a roller weighing 4.5 pounds and the product was labeled Cond 1.
[0092] Standard Temperature (ST) Example 1
[0093] 83 parts of AcResin 250 manufactured by BASF were charged into a planetary mixer preheated to 280°F. 17 parts of Citroflex A4 were slowly added to the mixer and the mixture was stirred at 280°F for 30 minutes. The mixture was then degassed and discharged into a 5 gallon bucket. The resulting adhesive was uniform, clear and free of bubbles.
[0094] 5 gallon buckets containing adhesive are placed under 5 gallon bucket melters Alta Pail II (Nordson company) for UV-hot melt processing. The temperature setting of Alta Pail is 220 ° F, so that the adhesive is melted and pumped to the adhesive container where the temperature remains at 220 ° F. Then, the adhesive is pumped into the slot die from the adhesive container with a thickness of 16 mils. 5 mil adhesives are deposited on 76 pounds of multi-clad release liners, and by UV light chamber (H+ bulb from Heraeus company). The UVC dosage recorded by EIT UV Puck II is 90mJ / cm 2 .
[0095] The inside of 8 mil TPO-based waterproof backing membrane MC900MJZ manufactured by Charter NEX was corona treated to produce a surface energy of 40 dynes / cm2. The cured adhesive was laminated to the crystal corona treated side of the Charter NEX film using a roller weighing 4.5 pounds, and the product was labeled Cond 2. Physical properties were tested.
[0096] ST Example 2
[0097] Pure AcResin 260 without any plasticizer Citroflex A4 was subjected to 90 mJ / cm 2 The UVC dose of 1000 W was processed at an adhesive thickness of 5 mils. The adhesive was laminated to Charter NEX film and the product number was marked as Cond 3.
[0098] ST Example 3
[0099] Pure AcResin 250 without any plasticizer Citroflex A4 was subjected to 90 mJ / cm 2 The UVC dose of 1000 W was processed at an adhesive thickness of 5 mils. The adhesive was laminated to Charter NEX film and the product number was marked as Cond 4.
[0100] The following table shows a comparison between the CT formulation and ST Examples 1, 2 and 3.
[0101] CT Example ST Example 1 ST Example 2 ST Example 3 Acrylic polymer-AcResin 260 83 100 Acrylic polymer-AcResin 250 83 100 Plasticizer-Citroflex A4 17 17 <![CDATA[Required UVC dose (mJ / cm 2 )]]> 90 90 90 90
[0102] The table below shows a comparison between flashing strip constructions.
[0103] With ID Cond 1 Cond 2 Cond 3 Cond 4 Backing ID MC900MJZ MC900MJZ MC900MJZ MC900MJZ Adhesive Thickness (mils) 5 5 5 5 Adhesive preparations CT Example ST Example 1 ST Example 2 ST Example 3
[0104] 90° peel adhesion on OSB was evaluated at 73°F. The tape and board were conditioned at 73°F and 50% humidity for at least 2 hours. The tape was applied to the board at 73°F, rolled on a roller, and finger pressure was applied to press the tape onto the OSB surface. The tape was allowed to dwell on the OSB board at 73°F for 20 minutes and the 90° peel adhesion was measured at 73°F.
[0105] Shear is evaluated at 73°F (PSTC 107 / Procedure A). 1" wide strips are applied to standard steel plates under controlled rolling. Pressure is applied using either a mechanically operated 41 / 2 lb roller or a manually operated, PSTC approved 4.5 lb rubber roller. The plate is mounted vertically, a 1 kg standard mass is attached to the free end of the strip, and the time to failure is determined.
[0106] The table below shows the data for Cond 1 to 4 at 73F for 90 peel on OSB and shear on steel.
[0107]
[0108] Comparing the peeling of Cond 1 to Cond 3 on OSB, it can be seen that the addition of 17% plasticizer Citroflex A4 has little effect on the peeling of OSB when compared to pure AcResin 260. Similarly, comparing Cond 2 to Cond 4, it can be seen that the addition of 17% plasticizer Citroflex A4 has little effect on the peeling of OSB when compared to pure AcResin 250.
[0109] The shear retention of the plasticized polymer is defined as follows: Shear retention (%) = shear of plasticized polymer / shear of pure polymer without plasticizer, where plasticized polymer = mixture of plasticizer Citroflex A4 + AcResin 260 or 250 polymer. Pure polymer = AcResin 260 or 250.
[0110] The Shear / Steel of pure AcResin 250 is about 4 times that of pure AcResin 260. Surprisingly, when 17% of the plasticizer Citroflex A4 is blended with 83% of the polymer (Acrein 260 or AcResin 250), the Shear / Steel trend is opposite to what one would expect. The shear time of AcResin 250 / Citroflex A4 is 7.6 minutes, while the shear time of AcResin260 / Citroflex A4 is 269.1 minutes. The Shear / Steel of the AcResin 260 / Citroflex A4 blend (Cond 1) is 35 times that of the AcResin 250 / Citroflex A4 blend (Cond 2). The shear retention rate of AcResin260 / Citroflex A4 is 70%, while the shear retention rate of AcResin 250 / Citroflex A4 is only 0.5%.
[0111] Thermal Shear at 150°F
[0112] CT preparations
[0113] 82 parts of AcResin 260 manufactured by BASF were charged into a planetary mixer preheated to 280°F. 18 parts of Citroflex A4 were slowly added to the mixer and the mixture was stirred at 280°F for 30 minutes. The mixture was then degassed and discharged into a 5 gallon bucket. The resulting adhesive was uniform, clear and free of bubbles.
[0114] 5 gallon buckets containing adhesive are placed under 5 gallon bucket melters Alta Pail II (Nordson company) for UV-hot melt processing. The temperature setting of Alta Pail is 220 ° F, so that the adhesive is melted and pumped to the adhesive container where the temperature remains at 220 ° F. Then, the adhesive is pumped into the slot die from the adhesive container with a thickness of 16 mils. 5 mil adhesives are deposited on 76 pounds of multi-clad release liners, and by UV light chamber (H+ bulb from Heraeus company). The UVC dosage recorded by EIT UV Puck II is 80mJ / cm 2 .
[0115] The inside of an 8 mil TPO-based waterproof backing membrane MC900MJZ manufactured by Charter NEX was corona treated to produce a surface energy of 40 dynes / cm2. The cured adhesive was laminated to the corona treated side of the Charter NEX membrane using a roller weighing 4.5 pounds and the product number was marked as SL120. Physical properties were tested.
[0116] ST preparation
[0117] 86 parts of AcResin 250 manufactured by BASF were charged into a planetary mixer preheated to 280°F. 14 parts of Citroflex A4 were slowly added to the mixer and the mixture was stirred at 280°F for 30 minutes. The mixture was then degassed and discharged into a 5 gallon bucket. The resulting adhesive was uniform, clear and free of bubbles.
[0118] 5 gallon buckets containing adhesive are placed under 5 gallon bucket melters Alta Pail II (Nordson company) for UV-hot melt processing. The temperature setting of Alta Pail is 220 ° F, so that the adhesive is melted and pumped to the adhesive container where the temperature remains at 220 ° F. Then, the adhesive is pumped into the slot die from the adhesive container with a thickness of 16 mils. 5 mil adhesives are deposited on 76 pounds of multi-clad release liners, and by UV light chamber (H+ bulb from Heraeus company). The UVC dosage recorded by EIT UV Puck II is 120mJ / cm 2 .
[0119] The interior of the 8 mil TPO-based waterproof backing membrane MC900MJZ manufactured by Charter NEX was corona treated to produce a surface energy of 40 dynes / square centimeter. The cured adhesive was laminated to the corona treated side of the Charter NEX membrane using a roller weighing 4.5 pounds, and the product number was marked as SL120. Physical properties were tested. 1 inch wide strips were applied to standard steel plates under controlled rolling. Pressure was applied using a mechanically operated 41 / 2 pound roller or a manually operated, PSTC-approved 4.5 pound rubber roller. The plate was vertically mounted in an oven at 150°F, a mass of 0.5 kg was attached to the active end of the strip, and the failure time was determined.
[0120] The table below shows the comparison between CT formulation and generic formulation.
[0121] CT Example ST Embodiment Acrylic polymer-AcResin 260 82 Acrylic polymer-AcResin 250 86 Plasticizer-Citroflex A4 18 14 <![CDATA[Required UVC dose (mJ / cm 2 )]]> 80 120
[0122] The table below shows a comparison between flashing strip structures.
[0123] With ID SL120 SL100 Backing ID MC900MJZ MC900MJZ Adhesive Thickness (mils) 5 5 Adhesive preparations CT Example ST Embodiment
[0124] from Figure 7 As can be seen in Figure 5, the thermal shear of SL120 at 150°F is approximately 7 times that of SL100. The surprisingly higher thermal shear of SL120 (using the CT example) indicates a synergistic effect of the plasticizer Citroflex A4 and the polymer AcResin 260.
[0125] Permeability
[0126] Following the procedure outlined above, 78 gsm PP nonwovens were laminated using 3, 5, and 8 mil adhesives formed from 82 parts AC-Resin 260 and 18 parts Citroflex A4. The permeability of the uncoated nonwovens and the nonwovens coated with adhesive was measured using ASTM E96B (wet cup method). The average permeability results are shown below:
[0127]
[0128] The exemplary embodiments have been described with reference to preferred embodiments. Obviously, others will think of modifications and changes after reading and understanding the above detailed description. It is intended that the exemplary embodiments be interpreted as including all such modifications and changes as long as they fall within the scope of the appended claims or their equivalents.
[0129] To assist the Patent Office and any reader of this application and any resulting patents in interpreting the appended claims of this application, Applicants do not intend to invoke 35 U.S.C. 112(f) with respect to any claim or claim element appended hereto unless the words "means" or "step" are expressly used in a particular claim.
Claims
1. Use of an adhesive composition in a building construction material selected from permeable and impermeable barriers, flashing tapes, sealing tapes, and double-coated tapes, wherein the adhesive composition is applied to the building material at a thickness of at least 3 mils and in a repeating or random pattern, the repeating or random pattern covering less than 100% of the surface, the adhesive composition comprising: a UV curable acrylic polymer having a molecular weight between 150,000 and 300,000 g / mol; and between 1 and 50 wt. % of a plasticizer having a molecular weight between 200 and 1000 g / mol; wherein the plasticizer is selected from the group consisting of citrates and acetates, and wherein the plasticizer transmits more UV radiation than the plasticizer does not transmit.
2. The use according to claim 1, wherein the adhesive composition comprises: a UV curable acrylic polymer having a molecular weight between 170,000 and 250,000 g / mol; and Between 8 and 20% by weight of plasticizer having a molecular weight between 300 and 700 g / mol.
3. Use according to claim 2, wherein the plasticizer has a molecular weight between 400 and 600 g / mol.
4. The use according to claim 1, wherein the adhesive composition comprises a λ of 250 to 260 nm. 最大 A UV curable polymer and a plasticizer that absorbs less than 5% of UV radiation at 250 to 260 nm.
5. The use according to claim 1, wherein the adhesive composition comprises a UV-curable polymer in combination with between 5 and 25% by weight of a plasticizer, the UV-curable polymer having a number average molecular weight M between 50,000 and 65,000 g / mol. n and / or a weight average molecular weight M between 100,000 and 200,000 g / mol w , the plasticizer has a molecular weight between 200 and 600 g / mol.
6. An article comprising a seaming tape, a flashing tape, a vapor permeable and impermeable weather barrier or a roof underlayment comprising an adhesive composition comprising a UV curable polymer in combination with between 2 and 30 wt. % of a plasticizer, the UV curable polymer having a number average molecular weight M between 50,000 and 65,000 g / mol n and / or a weight average molecular weight M between 100,000 and 300,000 g / mol w , the plasticizer has a molecular weight between 200 and 1000 g / mol, the plasticizer transmits more UV radiation between 200 and 360 nm than the plasticizer does not transmit, and wherein the plasticizer is selected from citrates and acetates, and wherein the adhesive composition has a thickness of at least 3 mils.
7. The article of claim 6 formed by transfer coating a cured UV pressure sensitive adhesive onto the article.
8. The article of claim 6, which is formed by directly coating and curing a pressure sensitive adhesive on the article.
9. The article of claim 8, wherein the transfer-coated substrate forms a release liner on the article.
10. The article of claim 8, wherein the transfer coated substrate is a sacrificial layer that is separated from the adhesive after UV curing and replaced by a release liner of a replacement composition.
11. The article of claim 8, wherein the article is treated to allow self-winding, wherein the transfer coated substrate is removed after curing.
12. The article of claim 6, comprising 100% adhesive coverage on the adhesive containing surface, wherein the article is vapor permeable after attachment to a building.
13. The article of claim 12 having an adhesive thickness of at least 8 mils and a permeability using ASTM E96B of at least 10.
Citation Information
Patent Citations
Nonwoven fiberous sheet of continuous strand material and the method of making same
US3169899A
Differentially bonded non-woven sheet
US3532589A
Oriented polymeric microporous films
US5317035A
Method of making fibrous, bonded polyolefin sheet
US5972147A
Water resistant fire retardant roof underlayment sheet material
US6641896B2